Generation Cohorts and Personal Values: A Comparison of China and the United States - Egri, Carolyn P.; Ralston, David A. (Organization Science, 2004)
This study investigated the generation cohort value orientations of 774 Chinese and 784 U.S. managers and professionals. The three Chinese generations (Consolidation, Cultural Revolution, Social Reform) since the establishment of Communist China were significantly more open to change and self-enhancement but less conservative and self-transcendent than the Republican Era generation. The value orientations of U.S. generations (Generation X, Baby Boomer, Silent generation) followed an age-related pattern with the exception of self-transcendence values. The least similar value orientations were between Chinese and U.S. generations that had grown up during Communist China's closed-door policy. The more entrepreneurial value orientations of the most recent Chinese generations appear to be compatible with organizational changes currently under way in China's state-owned sector.